MASKULINISASI IKAN GUPPY (Poecilia reticulata) MENGGUNAKAN EKSTRAK DAUN MENSIRAK (Ilex cymosa) MELALUI PERENDAMAN INDUK BUNTING - Ahmad Fahrul Syarif; Dendy Winardi; Robin (Universitas Mataram, 2021)
Freshwater ornamental fish commodities are in great demand by people in Indonesia, one of which is guppy fish (Poecilia reticulata). Guppies are very popular because they are easy to maintain and have beautiful color variations, especially for male guppy fish. The constraint in guppies cultivation is that the number of male chicks produced is usually lower than the number of females. The use of mensirak leaf extract is thought to be used in the process of masculinizing guppies. This study was conducted to determine the best dose of mensirak leaf extract to increase male sex ratio in guppies. The method used in this study is an experimental method using a single Completely Randomized Design (CRD) with 5 levels of treatment consisting of 3 replications. The immersion doses of female guppy broodstock used were P1 (2 mg/L), P2 (4 mg/L), P3 (6 mg/L), positive control 17?-methyltestosterone (2 mg/L) and negative control (0 mg/L). L). The results showed that the use of mensirak leaf extract immersing pregnant mothers had a significant effect on the percentage of male sex with the best concentration of 2 mg/L (45.93±27.19%). The masculinization of guppies using mensirak leaf extract on the immersion of pregnant guppy broodstock had a significant effect on the percentage of male sex. The best dose for immersing pregnant guppies using mensirak leaf extract was obtained in treatment P1 with a dose of 2mg/L, which resulted in the percentage of male sex being 45.93±27.19%.